Metamaterials: Electrically Controlled Nanostructured Metasurface Loaded with Liquid Crystal: Toward Multifunctional Photonic Switch (Advanced Optical Materials 5/2015). Issue 5 (May 2015) - Buchnev, Oleksandr; Podoliak, Nina; Kaczmarek, Malgosia; Zheludev, Nikolay I.; Fedotov, Vassili A.
<x xml:space="preserve">Abstract</x> On page 674, O. Buchnev, V. A. Fedotov, and co‐workers at the University of Southampton demonstrate an active, nanostructured, planar metamaterial functionalised with a nematic liquid crystal. For the first time, this metamaterial fully engages the mechanism of electrically controlled nanoscale in‐plane switching of the liquid crystal director, enabling control of both the magnitude and wavelength of the transmission.